2013
DOI: 10.1159/000354692
|View full text |Cite
|
Sign up to set email alerts
|

FLAIR-Only Progression in Bevacizumab-Treated Relapsing Glioblastoma Does Not Predict Short Survival

Abstract: Objectives: In this study, we analyzed the prognostic value of different MRI progression patterns for survival in patients with recurrent malignant glioma treated with the vascular endothelial growth factor antibody bevacizumab. Patients and Methods: Twenty-six adult patients with recurrent malignant glioma treated with bevacizumab or bevacizumab/irinotecan were retrospectively analyzed for the development of contrast-enhanced (T1-weighted MRI) and T2/FLAIR lesions. According to the progression pattern, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Whereas local tumor recurrence is associated with a better prognosis, the remaining recurrence patterns are associated with impaired overall survival 15 . Most studies focused on recurrence patterns in correlation to specific therapy regimes, especially bevacizumab that was thought to be associated with a more invasive recurrence pattern and often FLAIR-only recurrence 22 24 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas local tumor recurrence is associated with a better prognosis, the remaining recurrence patterns are associated with impaired overall survival 15 . Most studies focused on recurrence patterns in correlation to specific therapy regimes, especially bevacizumab that was thought to be associated with a more invasive recurrence pattern and often FLAIR-only recurrence 22 24 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of this study limits our ability to determine an association between early T2/FLAIR progression (alone or mixed with other change) and poorer outcomes. Other retrospective studies have resulted in conflicting findings related to whether T2/FLAIR tumor progression is adversely associated with survival . Although several have not found an association, a retrospective analysis of data from patients who participated in the recurrent glioblastoma AVF3708g clinical trial found that a T2/FLAIR assessment was significantly associated with differences in PFS and response rates .…”
Section: Discussionmentioning
confidence: 99%
“…Other retrospective studies have resulted in conflicting findings related to whether T2/FLAIR tumor progression is adversely associated with survival. [17][18][19] Although several have not found an association, a retrospective analysis of data from patients who participated in the recurrent glioblastoma AVF3708g clinical trial found that a T2/FLAIR assessment was significantly associated with differences in PFS and response rates. 20 Our study has not incorporated advanced MRI techniques such as diffusion restriction, spectroscopy, and cerebral blood volume assessments; it is acknowledged that because of the conflicting studies on the prognostic significance of T2/ FLAIR signal changes, advanced MRI may enlighten investigators and clinicians in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The volumetric methods were also not significantly different from each other. In the past, several studies on the added value of volumetry in recurrent glioblastoma in determining OS have been performed, 11,21,22 most notably by Boxerman et al, 13 in which a direct comparison is made between 2D and volumetric methods. We analyzed all patients together and the bevacizumab-treated patients separately.…”
Section: Discussionmentioning
confidence: 99%